Coronavirus: Impact on Stock Prices and Growth Expectations - Gormsen, Niels Joachim; Koijen, Ralph S J (The Review of Asset Pricing Studies, 2020)
Abstract We use data from aggregate stock and dividend futures markets to quantify how investors’ expectations about economic growth evolved across horizons following the outbreak of the novel coronavirus (COVID-19) and subsequent policy responses until July 2020. Dividend futures, which are claims to dividends on the aggregate stock market in a particular year, can be used to directly compute a lower bound on growth expectations across maturities or to estimate expected growth using a forecasting model. We show how the actual forecast and the bound evolve over time. As of July 20th, our forecast of annual growth in dividends points to a decline of 8% in both the United States and Japan and a 14% decline in the European Union compared to January 1. Our forecast of GDP growth points to a decline of 2% in the United States and Japan and 3% in the European Union. The lower bound on the change in expected dividends is -17% in the United States and Japan and -28% in the European Union at the 2-year horizon. News about U.S. monetary policy and the fiscal stimulus bill around March 24 boosted the stock market and long-term growth but did little to increase short-term growth expectations. Expected dividend growth has improved since April 1 in all geographies.